The Effect of Paper Reading Versus Screen Reading on the Inferential Reading Performance among University ESL Learners - Aziz, Musharraf; Hassan, Ahdi; Aljamili, Omar (Jurnal Arbitrer, 2024)
Contemporary ESL education focuses on screen-based reading, specifically in the context of university level learners. Also, a sudden shift from paper bound reading activities to screen-based tasks was inevitable in response to COVID-19 outbreak. In this regard, the case of inferential and advanced level reading among the young ESL learners of developing countries appears researchable because of the general low digital literacy of these learners. This study, therefore, aimed to investigate the effect of reading mode shift from paper to screen on the inferential comprehension performance among Pakistani ESL learners at university level. A total of 426 undergraduate learners were sampled from Bachelor of Science program in a well-known university in the city of Lahore, Pakistan. Inferential reading was conceptualized through Bloom’s higher order thinking skills, that is, Analyzing, Evaluating and Creating skills therefore the reading comprehension test was based on these skills. Adopting sequential test administration, first the paper-based reading test, and later the screen-based reading was given. The obtained data were analyzed using Rendell’s XCALIBRE and SPSS V. 26.0. The logit scale descriptives, learner ability (θ), and mean scores demonstrated that the learners performed significantly higher in the paper test as compared to screen test. Moreover, it was found that the effect of reading mode shift was larger in Creating skill. The findings may have significant implications for reading mode selection, enhancement of digital competence and effect of reading mode shift in developing countries with inadequate IT facilitation and digital literacy among ESL learners.